Stochastic security constrained unit commitment incorporating demand side reserve - Sahebi, Mir Mohammad Reza; Hosseini, Seyed Hamid (International journal of electrical power & energy systems, 2014)
•An energy and reserve market based on two-stage stochastic programming is proposed.•Spinning and demand side reserves are considered as operating reserve services.•Demand side (DS) reserve is modeled as emergency demand response program.•Demand side reserve causes reducing cost and increasing reliability significantly.•Increasing incentive price and electricity price would increase DS participation. Increasing the social welfare and achieving real competitive markets are the main purposes of consumers participation in electricity markets. Hence, Demand Response Programs (DRPs) have been designed to consider the consumers participation. One of these programs named Emergency Demand Response Program (EDRP) is based on consumers’ responses to high electricity prices and to the incentives that are paid by Independent System Operators (ISOs) in the critical hours. In this paper, a model has been proposed for EDRP participation in the Stochastic Security Constrained Unit Commitment (SCUC) program. Both the spinning reserve and the demand side reserve, which is modeled as EDRP, are taken into account as the operating reserve services. The effects of EDRP and its parameters on the system operation cost have been investigated under power system uncertainties. The two-stage stochastic SCUC model has been utilized for simultaneous clearing of energy and reserve markets. Mixed Integer Linear Programming (MILP) has been used for modeling the proposed method in the GAMS (General Algebraic Modeling System) environment. The proposed model is applied to a 6-bus test system and a modified IEEE Reliability Test System (RTS) to demonstrate its effectiveness.